Perancangan Pengalaman Pengguna Aplikasi Jasa Digital Printing di Kabupaten Banyuwangi berbasis Mobile menggunakan Human-Centered Design - Ahmad Wildan Jauhari; Riswan Septriayadi Sianturi; Agi Putra Kharisma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The digital printing business that continues to grow makes entrepreneurs want to open a business in the digital printing world. Banyuwangi Regency is one of the districts that has several printers. Of the 50 promotion respondents in Banyuwangi Regency, they found that respondents experienced problems with printing services such as the ordering process, product search, product payment, and printing revenue withdrawals. a platform that connects printer owners and customers to solve these problems. Researchers designed the user experience for digital printing applications in Banyuwangi Regency using the human-centered design method. The Human-Centered Design (HCD) used includes analysis of user context, analysis of user needs, design of solution designs, and evaluation of solution designs. The result of the design solution is a high-fidelity prototype that is tested on the user. Testing was conducted using usability testing and a user experience questionnaire (UEQ). The results of usability testing have 3 aspects, namely the effectiveness aspect getting a score of 84.44%, the efficiency aspect getting a score of 0.059 tasks/second, and the user satisfaction aspect getting a score of 90, which is included in the grade A category with an adjective rate rating, namely